Phasing out Nuclear Power in Europe - Finn Roar Aune; Rolf Golombek; Hilde Hallre (Center for Economic Studies and ifo Institute (CESifo), 2015)
We explore the impact of an EU-wide nuclear phase-out by 2030 provided the EU energy and climate policy for 2030 is implemented. Using a numerical simulation model of the European energy industry (LIBEMOD), we find that a complete nuclear phase-out in Europe by 2030 has a moderate impact on total production of electricity (4 percent reduction) and only a tiny impact on total consumption of energy. Lower nuclear production is to a large extent replaced by more gas power and bio power. Whereas the 2030 EU target for the renewable share in final energy demand is (at least) 27 percent, we find that after a nuclear phase-out the renewable share is 29 percent. Total annual cost of a nuclear phase-out corresponds to 0.5 percent of GDP in Europe.
Keywords: Q28; Q41; Q42; Q48; Q54; 330; nuclear power; renewable electricity; CCS; carbon policy; energy modeling